Assessment of the rate of glomerular filtration by a non-invasive method - Sofiya Ruzhylo; Xawery Żukow; Dariya Popovych; Nataliya Zakalyak; Halyna Kovalchuk; Yuriy Rohalya; Oleg Masnyi (Kazimierz Wielki University, 2024)
Background. Existing methods for assessing glomerular filtration rate (GF) are invasive. Therefore, we set ourselves the goal of evaluating the rate of glomerular filtration by a non-invasive method. Materials and Methods. The object of observations were 10 men aged 37-69 years without clinical diagnosis tested twice with 7-days interval. The rate of glomerular filtration was calculated according to endogenous creatinine clearance and the Cockcroft & Gault formula. Systolic and diastolic blood pressure was measured three times in a row. The state of the autonomic nervous system was assessed by the HRV method. Results. We confirmed the significant correlation of GF with age and weight. The screening revealed a significant correlation of GF with a number of blood pressure and HRV parameters. If in the classic formula we replace creatinineemia with systolic blood pressure and HRV-markers of sympathetic tone, we get a formula for estimating the GF with a standard error of 10,9 mL/min vs 2,7 mL/min, but without blood sampling. The regression model, which includes HRV and blood pressure parameters, as well as urinary creatinine concentration, allows estimating GF with a standard error of 12 mL/min. Conclusion. The balneotherapy has a significant effect not only on blood creatinine level, but also on HRV and blood pressure parameters, and even more pronounced. Therefore, the estimation of GF based only on the Cockcroft & Gault formula is at least not much more accurate than the one proposed by us, besides, our method is completely non-invasive.